2014
DOI: 10.1007/s00127-014-0950-9
|View full text |Cite
|
Sign up to set email alerts
|

Demographic risk factors for suicide and depression among Serbian medical school students

Abstract: Our findings suggest that medical school students in Serbia may be considered an "at-risk" population. Preventative programs in the future should target symptoms of depression and should provide students with adequate mechanisms to cope successfully with school-related pressure. Alternative stress management strategies may also be useful, especially for younger students who seem to be at greater risk for depression and suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
5
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 14 publications
2
48
5
3
Order By: Relevance
“…Our data confirm previous studies (Lester, 2013; Nyer et al, 2013) in which no effects were found for lifetime death wish or suicidal ideation on (self-reported) AYP. They are also in line with recent findings (Miletic et al, 2015) in showing a significant association between suicide attempt and academic performance, and, in addition, a significant association between STB plans and reduction in GPA. This suggests that only severe STB, suicide plans and attempts, may have a negative impact on academic performance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data confirm previous studies (Lester, 2013; Nyer et al, 2013) in which no effects were found for lifetime death wish or suicidal ideation on (self-reported) AYP. They are also in line with recent findings (Miletic et al, 2015) in showing a significant association between suicide attempt and academic performance, and, in addition, a significant association between STB plans and reduction in GPA. This suggests that only severe STB, suicide plans and attempts, may have a negative impact on academic performance.…”
Section: Discussionsupporting
confidence: 93%
“…For example, no association was found between suicidal ideation and grade point average (GPA) in two smaller samples (Lester, 2013; Nyer et al, 2013). A larger study of 1296 medical students (Miletic et al, 2015) found that those with lifetime suicidal ideation and/or suicide attempt(s) had a lower GPA as compared to those who never experienced STB (7.90 vs. 8.24; p =0.001). Unfortunately, no separate analyses were conducted for those with more severe STB (e.g., plans or attempts), and those with suicidal ideation only, although a Spearman's coefficient of −1.25 ( p <0.001) was found between GPA and severity of suicidal behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Medical schools are known to be environments associated with stressors and factors that negatively impact academic performance as well as both physical and emotional health of students. 9,22,23 With regard to the changes in mental health found for the different semesters, students from the first semester commenced activities with a high level of anxiety, exceeding that of students from the tenth and eleventh semesters, most likely stemming from the experience of the unknown, from the expectations of embarking on this new path, and from moving away from home (as it happens to most students in our university). Miller et al, 24 investigating first-year students, postulated that stress in this group stemmed from the nature and overload of the work inherent to the medical course, as well as from the academic structure of the course and its teaching methods.…”
Section: Discussionmentioning
confidence: 99%
“…Der Cronbachs Alpha von Originalversion und deutscher Übersetzung liegt zwischen 0,86 und 0,89 [20][21][22]. Offizielle Übersetzungen des PHQ liegen auch für die im Rahmen dieser Studie genutzten zusätzlichen Sprachen vor [23][24][25][26][27][28]. Fehlende Werte auf dem PHQ wurden gemäß Empfehlung durch den Wert "0" (nicht relevant) ersetzt [20].…”
Section: Instrumenteunclassified